Praet, Stijn, and Anna Kérchy, eds. The FairyTale Vanguard: Literary Self-Consciousness in a Marvelous Genre. Newcastle upon Tyne: Cambridge Scholars, 2019. 290 pp. - Rusvai, Mónika (FOCUS: Papers in English Literary and Cultural Studies, 2020)